درجة مكافحة الفساد وأثرها في بناء القوة الناعمة - الأورفلي خضر; حاووط عزّ الدين (Latakia University Journal - Economic and Legal Sciences Series, 2016)
This research is an attempt to introduce the concept of soft power, then show the extent to which affect the fight against corruption in the construction of soft power processes, beginning displays Find concept of soft and definition of power, then the scientific importance, which is trying to illustrate the growing importance of soft in the modern international relations of force with highlight on the causes of this growing scientific interest and practical interest in this concept, the following, the analytical presentation of the relationship between the degree of anti-corruption index and soft power index in many countries of the world that have the indication of soft power between the years 2010 and 2012, through statistical analysis using statistical data analysis software SPSS to know independent variable effect on the dependent variable, and then assemble states according to two groups using cluster analysis to see which countries it invests high degrees in the fight against corruption and which invests low-grade and see if there are significant differences between the two countries will use the independent analysis of the samples tested, is finally results and discussion. هذا البحث هو محاولة لطرح مفهوم القوة الناعمة وأهميته، ومن ثم إظهار إلى أي مدى تؤثر عملية مكافحة الفساد في بناء القوة الناعمة. بداية يعرض البحث مفهوم القوة الناعمة وتعريفها، ثم الأهمية العلمية التي تحاول توضيح تنامي أهمية القوة الناعمة في العلاقات الدولية الحديثة مع تسليط الضوء على مسبّبات تنامي هذه الأهمية العلمية والاهتمام العملي بهذا المفهوم، يلي ذلك، عرض تحليلي للعلاقة بين مؤشر درجة مكافحة الفساد ومؤشر القوة الناعمة لدى العديد من دول العالم التي تملك مؤشراً للقوة الناعمة بين أعوام 2010 و2012، من خلال تحليل إحصائي بالاستعانة ببرنامج تحليل البيانات الإحصائي SPSSلمعرفة أثر المتغير المستقل على المتغير التابع، ومن ثم تجميع الدول وفق مجموعتين باستخدام التحليل العنقودي لمعرفة أي الدول التي تستثمر بدرجات مرتفعة في مكافحة الفساد وأيّها يستثمر بدرجة منخفضة, ومعرفة ما إذا كان هناك فروق جوهرية بين مجموعتي الدول، إذ سيتم استخدام اختبار تحليل العينات المستقلة، أخيراً يتم عرض النتائج ومناقشتها.